Regional Variation in Kemp’s Ridley Sea Turtle Diet Composition and Its Potential Relationship With Somatic Growth - Ramirez, Matthew D.; Avens, Larisa; Goshe, Lisa R.; Snover, Melissa L.; Cook, Melissa; Heppell, Selina S. (Frontiers in Marine Science, 2020)
Reptile growth is influenced by many ecological processes that can cumulatively give rise to divergent somatic growth rates within spatially structured populations. As somatic growth variation can strongly influence a species’ population dynamics, identifying proximate drivers can be critical to the conservation and management of protected species. Kemp’s ridley sea turtles (Lepidochelys kempii) exhibit spatial variation in both diet composition and growth, but whether components of this variation are linked has not been evaluated. Through an integration of skeletochronological and stable isotope analyses of stranded turtle humerus bones we characterized regional variation in Kemp’s ridley diet composition and potential relationships with somatic growth rates. Turtles were divided among five regions within the U.S. Gulf of Mexico (GoM) and Atlantic Coast based on location of stranding, and humerus bones were sampled for stable carbon (δ13C) and nitrogen (δ15N) isotope ratios. These data were combined with region-specific prey stable isotope data sourced from the primary literature into Bayesian stable isotope mixing models (MixSIAR) to estimate the proportional contribution of five prey groups (crustaceans, bivalves, gastropods, fish, macroalgae/seagrass) to Kemp’s ridley diets. Our analysis revealed strong regional differences in mixing model-derived diet composition estimates that closely tracked published records of Kemp’s ridley diet. Invertebrates generally comprised the largest proportion (43.5–97.7 %) of turtle diets. However, we also observed high proportional contributions of fish (42.6–43.1 %) to western GoM turtle diets and macroalgae/seagrass (42.4–47.8 %), or isotopically similar prey resources (e.g., tunicates), to eastern GoM turtle diets. Growth rates were poorly correlated with δ15N values—a proxy for trophic level—and diet composition estimates, suggesting that diet composition alone may not explain the regional differences in somatic growth observed in this species. This study highlights the value of complementary skeletal and isotopic analyses to understanding regional diet variation in sea turtles as well as the importance of continued collection of isotopic data for both sea turtles and their prey. These results also help fill critical knowledge gaps pertaining to the relationship between sea turtle foraging ecology and somatic growth dynamics, a topic of high importance to sea turtle conservation and management.